2016
DOI: 10.1007/s10096-016-2807-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of ceftaroline against methicillin-resistant Staphylococcus aureus (MRSA) isolates collected in 2013–2014 at the Geneva University Hospitals

Abstract: Ceftaroline is a broad-spectrum antibiotic with activity against methicillin-resistant Staphylococcus aureus (MRSA) strains. Ceftaroline susceptibility of an MRSA set archived between 1994 and 2003 in the Geneva University Hospitals detected a high percentage (66 %) of ceftaroline resistance in clonotypes ST228 and ST247 and correlated with mutations in PBP2a. The ceftaroline mechanism of action is based on the inhibition of PBP2a; thus, the identification of PBP2a mutations of recently circulating clonotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…after the collection of these strains, these findings are worrisome. Previous studies indicated that CPT resistance could be associated not just with the source country of specific isolates 19 , 21 , 22 , 24 , 25 but also with the MLST profile 55 ; conversely, however, the CPT-resistant isolates analyzed in this study had diverse MLST profiles, including ST-8, ST-5 (the most common in the USA), ST-45, ST-72, ST-105, ST-474, ST-512, and ST-1075, indicating no such specificity for sequence type. In addition, isolates in this study tended to be concurrently resistant to both MER and CPT regardless of MLST.…”
Section: Discussionmentioning
confidence: 99%
“…after the collection of these strains, these findings are worrisome. Previous studies indicated that CPT resistance could be associated not just with the source country of specific isolates 19 , 21 , 22 , 24 , 25 but also with the MLST profile 55 ; conversely, however, the CPT-resistant isolates analyzed in this study had diverse MLST profiles, including ST-8, ST-5 (the most common in the USA), ST-45, ST-72, ST-105, ST-474, ST-512, and ST-1075, indicating no such specificity for sequence type. In addition, isolates in this study tended to be concurrently resistant to both MER and CPT regardless of MLST.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftaroline has a broad range of activity (Table 1). However, both low-level [3] and high-level [4] resistance to ceftaroline have been observed in MRSA strains; particularly concerning are recent reports of resistance discovered in clinical MRSA isolates from patients in geographic regions never exposed to the drug [5,6]. Little is known of ceftaroline's ecological impact, though it is expected to be minor, as the drug is not excreted in the faeces [7].…”
Section: Ceftarolinementioning
confidence: 99%
“…In a study performed on 8037 S. aureus, four isolates were reported as CPT-NS strains which were susceptible to linezolid and vancomycin, and belonged to SCCmec types III [31]. In a study from Switzerland, 24% (23/96) of MRSA collected from deep infections, blood cultures, and superficial infections with MIC≥ 2 mg/L were reported as CPT-NS [32]. In the Atlas program, in which the ceftaroline susceptibility of S. aureus isolates from different countries was tested, 93.7% of the isolates were susceptible to this antibiotic, 5.9% were susceptible-dose dependent (SDD) and only 0.4% (263/61,045) were found to be resistant.…”
Section: Discussionmentioning
confidence: 99%